Pengembangan Kegiatan MINI-LAB pada Topik Ekologi dan Lingkungan Untuk Siswa Kelas X SMA - Crysty, Verronicha; Manurung, Binari; Syarifuddin, Syarifuddin (Magister Pendidikan Biologi, Universitas Negeri Medan, 2017)
This research aimed to develop a Mini-Lab on ecology and environment topics based on scientific literacy and local potential of North Sumatera which is feasible empirically. Feasibility of learning material is obtained through validation of content experts, design expert, assessment from biology teacher and students response to product that developed. This research and development used Borg and Gall model. However this study was limited to preliminary field testing only. Data validation and the questionnaire responses of teachers and students were analyzed descriptively qualitative. The result showed that according to content experts, the feasibility of product content was very good with average percentage score 93.32%. Feasibility of Mini-Labâs design that has been developed based on design expert was also very good with a percentage score of 91.66%. Result of biology teacher assessment on Mini-Lab activity on ecology and environment topics for X grade of senior high school students was developed with 93.75% (very good). Students response to the preliminary field testing individual testing is 80.35% (good), small group trial 84.52% (very good) and big group 91.38%.(very good).